Pengaruh Pengetahuan Perpajakan Dan Teknologi Informasi Perpajakan Terhadap Kepatuhan Wajib Pajak - Nuril Aspa; Wizanasari Wizanasari (Jaanur Elbarik Indonesia, 2026)
This research aims to determine the influence of Tax knowledge and Tax Information Technology on Taxpayer compliance. The population in this research is the Pondok Aren Primary Tax Service Office in 2024, namely 441,943 thousand individual taxpayers. With a sampling technique using the slovin formula, 100 respondents met the requirements. So the data analyzed amounts to 100 sample data. The data used in this research is primary data. The variables used in this research are Tax Knowledge (X1) as the first independent variable, and Tax Information Technology (X2) as the second independent variable and Taxpayer Compliance (Y) as the dependent variable. Based on the results of simultaneous hypothesis testing, it shows that Tax Knowledge and Tax Information Technology jointly influence Taxpayer Compliance. The results of partial hypothesis testing show that Tax Knowledge influences Taxpayer Compliance, and Tax Information Technology also influences Taxpayer Compliance.